2019 25th IEEE International Symposium on Asynchronous Circuits and Systems (ASYNC) 2019
DOI: 10.1109/async.2019.00019
|View full text |Cite
|
Sign up to set email alerts
|

Transistor-Level Analysis of Dynamic Delay Models

Abstract: Delay estimation is a crucial task in digital circuit design as it provides the possibility to assure the desired functionality, but also prevents undesired behavior very early. For this purpose elaborate delay models like the Degradation Delay Model (DDM) and the Involution Delay Model (IDM) have been proposed in the past, which facilitate accurate dynamic timing analysis: Both use delay functions that determine the delay of the current input transition based on the time difference T to the previous output on… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 13 publications
0
1
0
Order By: Relevance
“…One point deliberately neglected in this paper is accuracy. Investigations by Öhlinger et al [4] and Maier et al [7] revealed that deriving appropriate description is a nontrivial task. Furthermore, characterizing each single gate by relying heavily on analog simulations is computationally expensive.…”
Section: Discussionmentioning
confidence: 99%
“…One point deliberately neglected in this paper is accuracy. Investigations by Öhlinger et al [4] and Maier et al [7] revealed that deriving appropriate description is a nontrivial task. Furthermore, characterizing each single gate by relying heavily on analog simulations is computationally expensive.…”
Section: Discussionmentioning
confidence: 99%